Cellular mechanisms of frontal bone development in spotted gar (Lepisosteus oculatus). Issue 11 (6th May 2021) - Enny, Alyssa; Shanabag, Anusha; Thompson, Andrew W.; Racicot, Brett; Braasch, Ingo; Nakamura, Tetsuya
Abstract: Background: The cellular and molecular mechanisms initiating vertebrate cranial dermal bone formation is a conundrum in evolutionary and developmental biology. Decades of studies have determined the developmental processes of cranial dermal bones in various vertebrates and identified possible inducers of dermal bone. However, evolutionarily derived characters of current experimental model organisms, such as non‐homologous frontal bones between teleosts and sarcopterygians, hinder investigations of ancestral and conserved mechanisms of vertebrate cranial dermal bone induction. Thus, investigating such mechanisms with animals diverging at evolutionarily informative phylogenetic nodes is imperative. Results: We investigated the cellular foundations of skull frontal bone formation in the spotted gar Lepisosteus oculatus, a basally branching non‐teleost actinopterygian. Whole‐mount bone and cartilage staining and hematoxylin‐eosin section staining revealed that mesenchymal cell condensations in the frontal bone of spotted gar develop in close association with the underlying cartilage. We also identified novel aspects of frontal bone formation: enrichment of F‐actin, cellular membranes, and E‐cadherin in condensing cells, and extension of podia‐like structures from osteoblasts to the frontal bone, which may be responsible for bone mineral transport. Conclusion: This study highlights the process of frontal bone formation with dynamic architectural changes of mesenchymal cells in spotted gar, an emerging non‐teleost fish model system, illuminating supposedly ancestral and likely conserved developmental mechanisms of skull bone formation among vertebrates. Key Findings: The precise developmental staging of the cranial dermal bones in spotted gar was established. Mesenchymal cell condensations for the frontal bone develop in close association with the underlying cartilage. Enrichment of F‐actin, cellular membranes, and E‐cadherin takes place in condensing mesenchymal cells for the frontal bone.